A Novel G385E Variant in the Cold Region of the T3-Binding Domain of Thyroid Hormone Receptor Beta Gene and Investigations to Assess Its Clinical Significance. Issue 6 (30th December 2019) - Korwutthikulrangsri, Manassawee; Dosiou, Chrysoula; Dumitrescu, Alexandra M.; Refetoff, Samuel
Abstract : Background: Resistance to thyroid hormone beta (RTHβ) is characterized by elevated thyroid hormone and unsuppressed thyroid-stimulating hormone (TSH), caused by thyroid hormone receptor beta gene ( THRB ) defects. Most mutations producing RTHβ phenotype are located in CG-rich regions of THRB, encoding the T3-binding and hinge domains of the receptor. However, a region encompassing codons 384–425 is virtually devoid of RTHβ-causing mutations, termed "cold region." Case: A 49-year-old woman was diagnosed with Hashimoto thyroiditis in her twenties, and levothyroxine (LT4) was initiated. During LT4 treatment she had slightly elevated free thyroxine and TSH levels, suggesting the possibility of RTHβ. Results: Sequencing of THRB identified a heterozygous missense variant c.1154G>A producing p.G385E in the proband. Since this variant of unknown significance (VUS) has not been reported in RTHβ individuals and considering its location in the "cold region" of THRB, we questioned its relevance. In silico functional prediction algorithms showed conflicting results: PolyPhen-2 predicted this VUS to be probably damaging with a score of 1.000, while SIFT predicted it to be tolerated with a score of 0.07, thus making additional investigations necessary. Genotyping of family members revealed that the proband's mother and sister, without RTHβ phenotype, also harbored the same variant. This indicates that the THRB G385E variant is unlikely to manifest RTHβ phenotype and confirms its "cold" status. Conclusions: This study illustrates that assigning causality of a THRB VUS for RTHβ based only on in silico prediction algorithms is not always fully reliable. Additional phenotype-genotype segregation in family members can assist in predicting functional consequences of missense mutations.